Foundations of Geometry-III - Adhikary, Pushpa Raj (Kathmandu University Journal of Science, Engineering and Technology, 2010)
DOI: 10.3126/kuset.v4i1.2889 Kathmandu University Journal of Science, Engineering and Technology Vol.4, No.1, September 2008, pp 95-97